The Karyotype of Holoaden luederwaldti (Anura, Strabomantidae), with Report of Natural Triploidy - Campos, J. R. C. [UNESP]; Martins, I. A.; Haddad, Celio Fernando Baptista [UNESP]; Kasahara, S. [UNESP] (Charles Univ Prague, First Faculty Medicine, 2012)
The genus Holoaden includes three species described so far, but the only published cytogenetic data is from Holoaden bradei, with the karyotype 2n = 18, based on conventional staining. In the present paper we report, for the first time, data on chromosomes of H. luederwaldti, which presented 2n = 18 and a case of natural triploidy, with 2n = 3x = 27. In this sample, another karyotypic variation was observed due to the occurrence of two types of chromosome 8, which present submetacentric or subtelocentric morphologies. Homomorphic subtelocentric or heteromorphic condition was observed among the diploid specimens, whereas the triploid had one submetacentric and two subtelocentric chromosomes 8. In all specimens, Ag-NOR was located in the long arms of chromosomes 8, at the interstitial region when subtelocentric, or in the proximal region when submetacentric, confirmed by fluorescent in situ hybridization with the HM123 probe. The C bands showed centromeric distribution and distribution at Ag-NOR site. The centromeric heterochromatin was fluorescent with DAPI staining, whereas the Ag-NOR displayed bright fluorescence with CMA(3). Fluorescent in situ hybridization using a telomeric probe labelled exclusively the telomere regions. Although the same 2n = 18 chromosome numbers have been observed in H. luederwaldti and H. bradei, some differences in both karyotypes can be visualized, mainly with regard to the morphology of the last chromosome pairs.
Keywords: cytogenetics polyploidy; Terrarana; chromosome; Amphibia; FISH